Actual autonomy in the practice of nursing care of people with intellectual functioning disorders – an outline of the issues - Zurzycka, Patrycja; Puto, Grażyna; Radzik, Teresa (Nursing Problems / Problemy Pielęgniarstwa, 2018)
Respect for autonomy in the context of provided care constitutes one of the key elements of contemporary medical practice. In the decision-making process, autonomy is conceived as the ability to decide consciously, intentionally, with the understanding of all aspects related thereto and without any external influence. In view of intellectual disability resulting from congenital or developmental disorders as well as related to dementia disorders, the use of traditional autonomy criteria in decision making seems unrealistic and limits the independence of individuals. Therefore, the issue of actual autonomy is raised more and more frequently because it enables active co-participation in the care and therapeutic process of people who do not meet all the criteria necessary to give informed consent. The paper is aimed at presenting some selected issues pertinent to actual autonomy in the care of people with disorders in intellectual functioning.